Positioning SUMO as an immunological facilitator of oncolytic viruses for high-grade glioma - Karandikar, Paramesh V.; Suh, Lyle; Gerstl, Jakob V. E.; Blitz, Sarah E.; Qu, Qing Rui; Won, Sae-Yeon; Gessler, Florian A.; Arnaout, Omar; Smith, Timothy R.; Peruzzi, Pier Paolo; Yang, Wei; Friedman, Gregory K.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Oncolytic viral (OV) therapies are promising novel treatment modalities for cancers refractory to conventional treatment, such as glioblastoma, within the central nervous system (CNS). Although OVs have received regulatory approval for use in the CNS, efficacy is hampered by obstacles related to delivery, under-/over-active immune responses, and the “immune-cold” nature of most CNS malignancies. SUMO, the Small Ubiquitin-like Modifier, is a family of proteins that serve as a high-level regulator of a large variety of key physiologic processes including the host immune response. The SUMO pathway has also been implicated in the pathogenesis of both wild-type viruses and CNS malignancies. As such, the intersection of OV biology with the SUMO pathway makes SUMOtherapeutics particularly interesting as adjuvant therapies for the enhancement of OV efficacy alone and in concert with other immunotherapeutic agents. Accordingly, the authors herein provide: 1) an overview of the SUMO pathway and its role in CNS malignancies; 2) describe the current state of CNS-targeted OVs; and 3) describe the interplay between the SUMO pathway and the viral lifecycle and host immune response.